2016
DOI: 10.1097/dbp.0000000000000339
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Concerns as They Relate to Their Child's Development and Later Diagnosis of Autism Spectrum Disorder

Abstract: Objective Data from a toddler screening study were used to examine: 1) categories of concerns regarding the development of their child reported by parents prior to diagnostic evaluation, 2) congruence of parent concerns with their child’s later diagnosis, 3) the extent to which parent concern(s) were associated with the therapies their child received and types of specialists consulted, and 4) the association between the number of parental concern categories and clinical measures. Methods Toddlers who screene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
61
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 25 publications
14
61
2
1
Order By: Relevance
“…This result corroborates the ndings of Richards et al They reported that over 90% (n=532) of the parents brought up concerns during well child visits and 78.6% were about speech and verbal communication [29]. Children whose parents expressed concerns about their child's verbal communication experienced earlier ages for all outcomes when compared to children of parents who did not have verbal communication concerns [30]. Such nding highlights the evolution of parental concerns over time.…”
Section: Discussionsupporting
confidence: 87%
“…This result corroborates the ndings of Richards et al They reported that over 90% (n=532) of the parents brought up concerns during well child visits and 78.6% were about speech and verbal communication [29]. Children whose parents expressed concerns about their child's verbal communication experienced earlier ages for all outcomes when compared to children of parents who did not have verbal communication concerns [30]. Such nding highlights the evolution of parental concerns over time.…”
Section: Discussionsupporting
confidence: 87%
“…Parents early concern about their child's late achievement of developmental milestones is highly correlated with the later diagnosis of a child's neurodevelopmental disorder (e.g., Richards, Mossey & Robins, 2016). Richards et al, (2016) reported that the most common concern of parents was their child's lateness in speech/communication development, and the authors cautioned professionals to take parent concern seriously during the diagnostic workup.…”
Section: Distinguishing Types Of Neurodevelopmental Disordersmentioning
confidence: 99%
“…While developmental variation in the population is to be expected, a cluster of behaviours or missed milestones ('red flags') can signal the presence of a potential underlying problem and may be indicative of disordered behaviour [20]. Parental 'prediction' of ASD diagnosis via problematic behaviours has been shown to be reliable, both in prospective and longitudinal studies [21,22] and in studies utilising retrospective population data [23,24].…”
Section: Introductionmentioning
confidence: 99%